Current Situation of the Presence of Dirofilaria immitis in Dogs and Humans in Bucaramanga, Colombia - Esteban-Mendoza, María Victoria; Arcila-Quiceno, Víctor; Albarracín-Navas, Javier; Hernández, Isabel; Flechas-Alarcón, María Camila; Morchón, Rodrigo (Frontiers in Veterinary Science, 2020)
The cardiopulmonary dirofilariosis caused by Dirofilaria immitis, is a vector-borne infection, which can be transmitted to humans. The main hosts are both domestic and wild canids. This species mainly occurs in tropical and subtropical climates, and temperature and humidity are the main factors that favor the presence and proliferation of culicid mosquitoes as vectors of the disease. There are few reports of cardiopulmonary dirofilariosis in dogs and humans in Colombia, a region with favorable climatic conditions which favours the presence of mosquitoes that act as vectors of the disease. Therefore, this study aimed to examine its current prevalence in dogs and the risk of human exposure to the disease in Bucaramanga, one of the most populated areas in Colombia located at the center of the country. Furthermore, its demographic and environmental characteristics could be useful as a study model for other similar locations and neighboring countries. Serum samples from 351 dogs and 506 humans from the Bucaramanga metropolitan area were analyzed. All dog samples were analyzed by Knott’s technique and tested with a commercial immunochromatographic to detect the presence of circulating antigens of D. immitis. Human samples were analyzed using a non-commercial ELISA test kit to detect IgG against the somatic antigens of adult D. immitis and Wolbachia. Positive results were further confirmed using western blot analysis. Thirty-eight dogs tested positive with a overall prevalence of 10.82%. Of these dogs, 18 showed D. immitis microfilariae, being 5.12% of the total population. The overall seroprevalence in humans was 6.71%; seroprevalence was significantly higher in individuals aged 16–34 years-old and in women than in men. To our knowledge, this study describes seropositivity to D. immitis for the first time in a Colombian human population located in the same area as that of dogs infected with D. immitis, which represents a potential threat to public health. In humans, age and gender can be considered risk factors for exposure to D. immitis.